2017
DOI: 10.1186/s12957-016-1077-0
|View full text |Cite
|
Sign up to set email alerts
|

Bulbar conjunctival metastasis from mucoepidermoid carcinoma of parotid—a case report and review of literature

Abstract: BackgroundMucoepidermoid carcinoma of salivary glands usually metastasizes to the lungs, liver, bone, brain, and skin. We report a rare case of distant metastasis of high-grade mucoepidermoid carcinoma of the parotid to the ipsilateral bulbar conjunctiva of the eye.Case presentationSixty-year-old male of Kashmiri origin presented to our tertiary care referral cancer institute with exophytic lesion of the left bulbar conjunctiva following his treatment for mucoepidermoid cancer of ipsilateral parotid gland, 9 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
1
Order By: Relevance
“…Rare cases of cutaneous metastasis of MEC originating from different sites, like the bronchi should be taken into account [3]. Yadav et al, reported a case of an exophytic lesion of the left bulbar conjunctiva following treatment for high grade mucoepidermoid cancer of ipsilateral parotid gland, 9 months back [15]. For this reason a careful evaluation of the patients to look for occult neoplasms in distant sites needs to be done.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rare cases of cutaneous metastasis of MEC originating from different sites, like the bronchi should be taken into account [3]. Yadav et al, reported a case of an exophytic lesion of the left bulbar conjunctiva following treatment for high grade mucoepidermoid cancer of ipsilateral parotid gland, 9 months back [15]. For this reason a careful evaluation of the patients to look for occult neoplasms in distant sites needs to be done.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason a careful evaluation of the patients to look for occult neoplasms in distant sites needs to be done. It is recommended to perform blood chemistry profile, complete blood count together with diagnostic imaging like total body Positron Emission Tomography and Computed Tomography Scan and p63 immunostaining to differentiate cutaneous metastasis from primary MEC [10,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Overt cytologic atypia or mitotic activity is absent and there are often prominent inflammatory cells in the background. 9 Yadav et al 10 have reported a case of metastatic MEC involving the bulbar conjunctiva from the parotid gland. No evidence of preexisting MEC was found in both cases on history and systemic workup.…”
Section: Discussionmentioning
confidence: 99%
“…In 1945, Stewart and associates described the mucous secreting and epidermal cellular component of mucoepidermoid carcinoma, thus establishing it as a distinct pathological entity [7]. Bhasker in 1963 reported 2 cases and analyzed the criteria for their central origin, histology and pathogenesis [1].…”
Section: Introductionmentioning
confidence: 99%